2020
DOI: 10.3389/fcell.2020.584898
|View full text |Cite
|
Sign up to set email alerts
|

Role of Cofilin in Alzheimer’s Disease

Abstract: Alzheimer’s disease (AD) is a degenerative neurological disease and has an inconspicuous onset and progressive development. Clinically, it is characterized by severe dementia manifestations, including memory impairment, aphasia, apraxia, loss of recognition, impairment of visual-spatial skills, executive dysfunction, and changes in personality and behavior. Its etiology is unknown to date. However, several cellular biological signatures of AD have been identified such as synaptic dysfunction, β-amyloid plaques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 186 publications
0
22
0
Order By: Relevance
“…[88] mention that Rho activation is essential for the dendritic spine functionality, cofilin phosphorylation, and, consequently, spine actin stabilization. According to Wang et al [89], cofilin phosphorylation prevents binding to the F-and G-actin binding, and only a dephosphorylated cofilin can initiate the actin-binding. Consequently, their activity is synchronized by phosphorylation/dephosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…[88] mention that Rho activation is essential for the dendritic spine functionality, cofilin phosphorylation, and, consequently, spine actin stabilization. According to Wang et al [89], cofilin phosphorylation prevents binding to the F-and G-actin binding, and only a dephosphorylated cofilin can initiate the actin-binding. Consequently, their activity is synchronized by phosphorylation/dephosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…A series of studies suggested that under conditions that cause cellular stress, complexes of actin and cofilin, so-called actin-cofilin rods, are formed and interfere with essential cell functions, and consequently were held responsible for causing the disease states ( Bamburg and Wiggan, 2002 ; Maloney and Bamburg, 2007 ; Bamburg et al, 2010 ; Munsie et al, 2011 ; Hoffmann et al, 2019 ; Wang et al, 2020 ). Experimental work also showed that formation of actin-cofilin rods can be provoked by various types of stressors either inside the nucleus or in the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…Rods can be formed either inside the nucleus or the cytoplasm. Cytoplasmic rods are associated with several neurodegenerative diseases like Alzheimer’s and Parkinson’s disease, variants of amyotrophic lateral sclerosis (ALS) ( Bamburg and Wiggan, 2002 ; Bamburg and Bernstein, 2010 ; Schonhofen et al, 2014 ; Bamburg and Bernstein, 2016 ; Wang et al, 2020 ), and spinal muscular atrophy (SMA) ( Walter et al, 2021 ). Intranuclear actin-cofilin rods were identified as hallmarks in muscle cells of patients with intranuclear rod myopathy (IRM), a specific form of nemaline myopathy ( Goebel and Warlo, 1997 ; Sparrow et al, 2003 ; Ilkovski et al, 2004 ; Domazetovska et al, 2007a ; Domazetovska et al, 2007 ), and Huntington’s disease (HD) ( Munsie et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…A series of studies suggested that under conditions that cause cellular stress, complexes of actin and cofilin, so-called actincofilin rods, are formed and interfere with essential cell functions, and consequently were held responsible for causing the disease states (Bamburg and Wiggan, 2002;Maloney and Bamburg, 2007;Munsie et al, 2011;Hoffmann et al, 2019;Wang et al, 2020). Experimental work also showed that formation of actin-cofilin rods can be provoked by various types of stressors either inside the nucleus or in the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…Rods can be formed either inside the nucleus or the cytoplasm. Cytoplasmic rods are associated with several neurodegenerative diseases like Alzheimer's and Parkinson's disease, variants of amyotrophic lateral sclerosis (ALS) (Bamburg and Wiggan, 2002;Schonhofen et al, 2014;Bamburg and Bernstein, 2016;Wang et al, 2020), and spinal muscular atrophy (SMA) (Walter et al, 2021). Intranuclear actin-cofilin rods were identified as hallmarks in muscle cells of patients with intranuclear rod myopathy (IRM), a specific form of nemaline myopathy (Goebel and Warlo, 1997;Sparrow et al, 2003;Ilkovski et al, 2004;Domazetovska et al, 2007a;Domazetovska et al, 2007), and Huntington's disease (HD) (Munsie et al, 2011).…”
Section: Introductionmentioning
confidence: 99%